Convergence of Economic Growth in The Bandung Metropolitan Area - Kharisma, Bayu; Wardhana, Adhitya; Hotma, Priscillya (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2024)
This study aims to determine the convergence and acceleration of growth to achieve steady-state conditions in the Bandung Metropolitan Area in 2010-2022. This research uses a quantitative descriptive approach by measuring variables and analyzing data statistically. Secondary data is used in this study to analyze convergence through panel data regression analysis and coefficient of variation. The results show that sigma convergence for the Bandung Metropolitan Area does not show convergence. The gap in the Bandung Metropolitan Area will decrease in less than 13 years. The absolute and conditional beta convergence results in the Bandung Metropolitan Area show convergence. Labor productivity is expected to accelerate economic growth due to the previous year's economic growth; the absolute beta convergence results do not significantly affect economic growth in the study year. Therefore, local governments are expected to focus on resource redistribution and infrastructure investment to increase the growth potential of lagging regions. In addition, investment in basic infrastructure such as roads, electricity, water, and health facilities should be increased in lagging regions to create conditions conducive to economic growth. Finally, encouraging inter-regional cooperation to share resources and knowledge can help lagging regions to catch up.